ANALISIS EFEKTIVITAS PROGRAM SUBSIDI MELALUI PUBLIC SERVICE OBLIGATION PADA SEKTOR TRANSPORTASI DARAT (STUDI KASUS PT TRANSPORTASI JAKARTA) - Limbong, Ramot Gideon Putra; Widanta, A.A Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2025)
This research aims to analyze the effectiveness of subsidy programs through Public Service Obligation (PSO) in the land transportation sector and identify their impact on the income of drivers at PT Jakarta Transportation. The research method involves collecting data through interviews with drivers, analyzing income data, and evaluating the implementation of the subsidy program. The results show that the subsidy program through PSO has a significant impact on drivers' income. There is an increase in income attributable to the increase in the number of passengers and the fares guaranteed by the subsidy program. The analysis of drivers' income data shows variation in the impact of the subsidy program, depending on factors such as routes, operational hours, and passenger occupancy levels. These factors need to be considered in designing subsidy policies to make them more equitable and sustainable for drivers.   Keywords  :  Public Service Obligation; Land Transportation; Subsidy; Program Effectiveness; Driver Income; PT Jakarta Transportation.